Nanomaterial Properties: Size and Shape Dependencies - Guisbiers, Grégory; Mejía Rosales, Sergio; Leonard Deepak, Francis (2012)
Nanoscience and nanotechnology are among the most widely used terms in the modern scientific and technological literature. The idea of nanotechnology appeared for the first time in the famous talk “There is plenty of room at the bottom” given by the physicist Richard Feynman at the American Physical Society meeting at Caltech on December 29, 1959. Feynman described a process by which the ability to manipulate individual atoms and molecules might be developed, using one set of precise tools to build and operate another proportionally smaller set and so on down to the needed scale. In the course of this, he noted, scaling issues would arise from the changing magnitude of various physical phenomena: gravity would become less important whereas surface effects would become increasingly more significant